2018
DOI: 10.1371/journal.pone.0207333
|View full text |Cite
|
Sign up to set email alerts
|

The influence of income and testosterone on the validity of facial width-to-height ratio as a biomarker for dominance

Abstract: Research has indicated that men's facial width-to-height ratio (fWHR) is part of an evolved system of social dominance, aggression, and power. fWHR has been linked to antisocial behavior, measured by self-reported aggression, but recent studies have failed to replicate this finding. To overcome these inconsistencies, influencing factors such as social status have to be taken into account in order to explain the relationship between fWHR and aggression. In particular, income has been shown to be an important in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…The authors theorized that sexual dimorphism in human fWHR might be driven by female mate choice for larger cheek bones ( Weston et al 2007 ), a feature indicative of facial attractiveness ( Cunningham 1986 ; Cunningham et al 1990 ), although other facial features may be stronger attractiveness indicators ( Mogilski and Welling 2018 ). Mate choice might not be the only driver of sexual dimorphism; fWHR may be a signal in male-male competition ( Carré and McCormick 2008 ), indicating differences in dominant and aggressive tendencies that could be linked to facial morphology through underlying differences in testosterone levels ( Lefevre et al 2013 ; Noser et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors theorized that sexual dimorphism in human fWHR might be driven by female mate choice for larger cheek bones ( Weston et al 2007 ), a feature indicative of facial attractiveness ( Cunningham 1986 ; Cunningham et al 1990 ), although other facial features may be stronger attractiveness indicators ( Mogilski and Welling 2018 ). Mate choice might not be the only driver of sexual dimorphism; fWHR may be a signal in male-male competition ( Carré and McCormick 2008 ), indicating differences in dominant and aggressive tendencies that could be linked to facial morphology through underlying differences in testosterone levels ( Lefevre et al 2013 ; Noser et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In both humans ( Goetz et al 2013 ; Noser et al 2018 ; Welker et al 2015 ) and capuchins ( Carré 2014 ) it has been suggested that the relationship between fWHR and aggressive behavior is driven by low social status, as it is significant only among low-status individuals. In brown capuchins, for example, although higher ranking individuals are typically higher in Assertiveness, correlations between fWHR and Assertiveness are significant only in non-alpha individuals ( Carré 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another study demonstrated the effects of social status moderated the association of fWHR and risk-taking behavior in males [36]. Noser et al found that income played a critical role in fWHR and physical aggression relation, so the authors suggested that social status had to be taken into account in such anthropometric studies [26].…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for those inconsistencies might range from sampling variations to the size of the study group, from ethnicity and socioeconomic status of the investigated population to the unstandardized measurement techniques used in anthropometric studies [26]. The measurement of fWHR as the sole anthropometric factor in most studies that investigate a link between facial features and aggression has also been considered to be responsible for inconsistent results [19].…”
Section: Introductionmentioning
confidence: 99%
“…When a study that assessed success in business as an ability to negotiate legitimately was added to the meta-analytic evaluation, the significant relationship between fWHR and business success that was reported in the literature was lost (18). Thus, since cheating is an antisocial behaviour, and positive association existed between business success (negotiation capacity using illegitimate approaches) and fWHR, higher fWHR predicts antisocial behaviour and personality (including psychopathy, Machiavellianism, and narcissism) (19). Although the behavioural traits of the study participants in the current study was not evaluated, nevertheless, the finding in the current study may putatively imply that the majority of them are unlikely to portray an antisocial behaviour such as cheating, because many of them have low fWHR and monthly income as compared to their counterpart.…”
Section: Discussionmentioning
confidence: 99%